2011
DOI: 10.1167/iovs.11-8517
|View full text |Cite
|
Sign up to set email alerts
|

Central Retinal Function as Measured by the Multifocal Electroretinogram and Flicker Perimetry in Early Age-Related Macular Degeneration

Abstract: Both mfERG and flicker perimetry show abnormal retinal function, but only in the very central macula, in early AMD. A novel relationship between mfERG and flicker sensitivity should enhance the clinical monitoring of disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 23 publications
1
42
1
Order By: Relevance
“…9,10 A measurement that has been of interest is the multifocal electroretinogram (mfERG), which allows an objective assessment of retinal function. 11 However, reports of mfERG findings in AMD have been inconsistent; some studies have reported significant functional deficits in the early stages of the disease, [12][13][14][15][16][17] whereas others have not. [18][19][20][21] This lack of consistency in findings may be attributed to the nonuniformity of disease severity and variation in the age of participants in different studies or differences in the techniques used to record the mfERG.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 A measurement that has been of interest is the multifocal electroretinogram (mfERG), which allows an objective assessment of retinal function. 11 However, reports of mfERG findings in AMD have been inconsistent; some studies have reported significant functional deficits in the early stages of the disease, [12][13][14][15][16][17] whereas others have not. [18][19][20][21] This lack of consistency in findings may be attributed to the nonuniformity of disease severity and variation in the age of participants in different studies or differences in the techniques used to record the mfERG.…”
Section: Resultsmentioning
confidence: 99%
“…1 Based on electrophysiological testing, it remains controversial whether rods are primarily affected or both rods and cones are similarly affected. [24][25][26][27][28][29][30][31][32][33] Microperimetry has detected photoreceptor abnormalities even before GA develops, and this strategy can also predict the area where existing GA will likely progress. [34][35][36][37][38][39][40] These histopathologic, electrophysiologic, and microperimetric findings in eyes with GA, along with the early visual function deficits and symptoms observed in patients even before GA develops, 41 suggest that photoreceptor dysfunction precedes the appearance and progression of GA in some eyes.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding mfERG, it is well known that dry AMD affects especially the central rings of the retina [15]. According to this feature, significant alterations in the central ring (ring 1) appear already after 1 year of evolution (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Several studies confirm that drusen presence affects the mfERG response. Thus, García-García et al [14] studied 25 individuals (10 AMD vs 15 control) concluding that drusen seems to be associated reported by other researchers [15,16]. However, other studies only found changes in the implicit time [17].…”
Section: Discussionmentioning
confidence: 92%